Diversification and determinants of international credit portfolios: Evidence from German banks - Benjamin Böninghausen; Matthias Köhler (Deutsche Bundesbank, 2012)
This paper examines the international credit portfolios of German banks. We construct a bank-country panel from a unique dataset for a representative set of countries and ask why banks leave diversification opportunities unexploited in some countries. Controlling for bank heterogeneity, we analyse the deviations of actual portfolios from a mean-variance based benchmark and their country-level determinants. Our results show that banking regulations are important determinants of the credit allocation of German banks. We present robust evidence that countries with stricter capital adequacy and entry requirements tend to be overweighted, primarily due to excess profits resulting from a lower level of banking market competition. German banks also overweight countries with larger and more developed banking markets. Moreover, we find support that German banks follow their domestic customers abroad to maintain existing lending relationships. Geographical factors, in contrast, do not seem to matter. Our findings suggest that changes in and convergence of banking regulations as well as financial deepening of banking sectors around the world may, in the long term, result in banks holding more diversified international credit portfolios.
Keywords: G21; G11; F36; F21; 330; international banking; international financial integration; portfolio choice